A Case Follow-Up Report: Possible Health Benefits of Extra Virgin Olive Oil. (2004) - Shahtahmasebi, Said; Shahtahmasebi, Shahnaz
Abstract : In the course of a case study, a number of issues regarding the dynamics of blood cholesterol levels were identified. In this follow-up report, these issues are addressed. For example, issues of past behaviour and seasonality, intraindividual variation, and nonstationarity appear important over and above controllable variables such as diet and exercise. In this report, we conceptualise an alternative protective role for the dynamic blood cholesterol levels in a healthy population. Furthermore, regular consumption of extra virgin olive oil as produced in this case study may interact with the dynamics of cholesterol naturally. We recommend that future studies of this kind ought to include a time series of blood cholesterol based on daily measurements or intervals much shorter than the bimonthly measurements and to include measures of overall well being as covariates.